ANALYSIS OF THE FINANCIAL SYSTEM MANAGEMENT OF MURABAHAH FINANCING PRODUCTS IN SHARIA PEOPLE'S FINANCING BANK (BPRS) CIVIL SYARIKAT IN BATAM CITY - Neri Aslina; Fithri Mehdini Addieningrum (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2023)
Murabaha financing is one of the financing programs for the community. The existence of murabaha financing provides financial support for people in need. The purpose of this research is to study the financial system related to the financial management of the Murabahah contract financing products offered by BPRS Syarikat Madani, Batam City. This research is a type of qualitative research or also known as case study research. Data collection tool is done through observation, interviews and documentation. The data analysis technique used is a qualitative data analysis technique. The results of the study show that the Syarikat Madani Islamic People's Financing Bank (BPRS) in Batam City uses a Murabahah contract as one of its main financing products. The management of Murabahah contract financing products is carried out in accordance with sharia principles. The Bank provides clear information to customers regarding the selling price, markup, tenor and terms of financing using the principles of transparency, fairness and sustainability.